2022
DOI: 10.1371/journal.pone.0269171
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, practice, and impact of COVID-19 on mental health among patients with chronic health conditions at selected hospitals of Sidama regional state, Ethiopia

Abstract: Background COVID-19 causes worse outcomes and a higher mortality rate in adults with chronic medical conditions. In addition, the pandemic is influencing mental health and causing psychological distress in people with chronic medical illnesses. Objective To assess the knowledge, practice, and impact of COVID-19 on mental health among chronic disease patients at selected hospitals in Sidama regional state. Method A facility-based cross-sectional study was conducted. A total of 422 study subjects were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…In addition, this study identified that lower education levels and lower income show a significant association with the problem. Furthermore, a study conducted in Brazil demonstrated that 65.1% of individuals reported an increase in unhealthy food intake and a decrease in the intake of fruits and vegetables among hypertensive patients [53] Moreover, the pandemic is also resulting in an increased prevalence of stress, anxiety, depression, and other mental health issues [13,15,16,38]. These findings are consistent with other studies conducted on the topic in different parts of the world [6,51].…”
Section: Discussionsupporting
confidence: 80%
“…In addition, this study identified that lower education levels and lower income show a significant association with the problem. Furthermore, a study conducted in Brazil demonstrated that 65.1% of individuals reported an increase in unhealthy food intake and a decrease in the intake of fruits and vegetables among hypertensive patients [53] Moreover, the pandemic is also resulting in an increased prevalence of stress, anxiety, depression, and other mental health issues [13,15,16,38]. These findings are consistent with other studies conducted on the topic in different parts of the world [6,51].…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, the pandemic is also resulting in an increased prevalence of stress, anxiety, depression, and other mental health issues [ 13 , 15 , 16 , 38 ]. These findings are consistent with other studies conducted on the topic in different parts of the world [ 6 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to WHO (2020), the negative impact of the COVID-19 pandemic on the psychological well-being of individuals with chronic diseases has not been uniform across different countries and populations. Factors such as the availability and quality of mental health care infrastructure, the degree of COVID-19 transmission, and the socio-economic status of the population have been identified as potential determinants of the impact of the pandemic on the psychological well-being of individuals with chronic diseases [ 13 , 15 , 16 , 38 ]. Overall, these findings highlight the importance of addressing the psychological well-being of individuals with chronic diseases during the COVID-19 pandemic [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation